KAPASITAS GESER BALOK BETON BERTULANG DENGAN OLYPROPYLENE FIBER SEBESAR 4% DARI VOLUME BETON - Apriyatno, Henry (Semarang State University, 2010)
Abstract:ÃÂ PolypropyleneÃÂ fiberÃÂ isÃÂ oneÃÂ ofÃÂ theÃÂ plasticÃÂ fiberÃÂ thatÃÂ hasÃÂ highÃÂ tensileÃÂ strength,ÃÂ easily available, relatively cheap, resistant to chemical attack, and has a dry surface so that no clumping of fiber in the concrete mixing process.The study aims to determine the effect of polypropylene fiber by 4% ofÃÂ the volume of concreteÃÂ to shear strength ofÃÂ reinforced concrete beams. The addition of polypropyleneÃÂ fiberÃÂ inÃÂ theÃÂ levelsÃÂ ofÃÂ 0%ÃÂ toÃÂ 4%ÃÂ ofÃÂ theÃÂ volumeÃÂ ofÃÂ concreteÃÂ causesÃÂ aÃÂ decreaseÃÂ in modulus of elasticity of 13966.33 MPa to 11,709 MPa. Shear test results reinforced concrete beam fiberÃÂ contentÃÂ increaseÃÂ fromÃÂ 0%ÃÂ to 4%ÃÂ increaseÃÂ inÃÂ capacityÃÂ obtainedÃÂ byÃÂ theÃÂ nominalÃÂ shearÃÂ beam from 4.08 tons to 4.56 tons. Fiber concrete beams will increase the shear capacity of 11.76% of the normal beam shear capacity. Keywords: polypropylene fiber, modulus elasticity, shear capacity ÃÂ Abstrak:ÃÂ ÃÂ PolypropyleneÃÂ fiber merupakan salah satu serat plastik yang memiliki kuatÃÂ tarikÃÂ tinggi, mudahÃÂ didapat,ÃÂ harganyaÃÂ ÃÂ ÃÂ relatifÃÂ murah,ÃÂ tahanÃÂ terhadapÃÂ seranganÃÂ bahanÃÂ kimia,ÃÂ danÃÂ memiliki permukaanÃÂ yangÃÂ keringÃÂ sehinggaÃÂ tidakÃÂ terjadiÃÂ penggumpalanÃÂ seratÃÂ dalamÃÂ prosesÃÂ pengadukan beton. PenelitianÃÂ bertujuan untuk mengetahui pengaruh penambahan polypropylene fiber sebesar 4% dari volum beton terhadap kuat geser balok beton bertulang. Penambahan polypropylene fiber dari kadar 0% sampai 4% dari volume beton menyebabkan penurunan nilai modulus elastisitas dari 13.966,33 MPa menjadiÃÂ 11.709 MPa. HasilÃÂ pengujianÃÂ geserÃÂ balokÃÂ betonÃÂ bertulangÃÂ penambahan kadar serat dari 0%ÃÂ sampai 4% diperolehÃÂ kenaikanÃÂ kapasitas geser nominal balok dari 4,08ÃÂ ton menjadi 4,56ÃÂ ton.ÃÂ ÃÂ Balok betonÃÂ fiber akan mengalami kenaikan kapasitas gesernya sebesar 11,76 % dari kapasitas geser balok normal. ÃÂ Kata kunci: polypropylene fiber, modulus elastis, kapasitas geser